Expressive Aspects of Restorative Dentistry - Yengonyan, Edgar; Jikia, Maia (Caucasus Journal of Health Sciences and Public Health, 2019)
The subject that will be reviewed is carrying a type of revolutionary character in operative, prosthetic and aesthetic dentistry in general, and its represents the field of restorative dentistry. As in all disciplines of dental medicine, evolution of this direction has already started from the day of its development, and as a rule in any type of evolutionary processes, there were certain key points during this path. In our case it’s the stage, which took place in history about a century ago. That was a period, during which were actively existences of such problems as: provision of ideal aesthetics, matching of opacity & translucency, provision of good biologic response compatible with soft tissues in subgingival margins, and not less important issue, alterations by corrosion